Identificación morfológica de poblaciones nativas de chirimoya con potencial agronómico en los cantones Saraguro y Quilanga - Erazo Hurtado, Jhandry Santiago (2024)
Since 1990 previous research in southern Ecuador have demonstrated samples in the wild and early stages of domestication with potential organoleptic and nutritious characteristics for further production and commercialization, but gradually its genetic erosion has increased. Thus, the morphologic identification of the native populations of chirimoya (Annona cherimola Mill) with high agronomic potential present in Saraguro and Quilanga arises as an essential requirement for its conservation. For this reason, we did a field prospecting locating the populations, plants and fruits were characterized using 37 quantitative descriptors and 33 qualitative. The hot zones were geographically identified resulting in 10 and 31 points for Saraguro and Quilanga respectively. Using descriptors with CV>20%, through cluster analysis 4 mains groups were identified. On the other hand, using fruit descriptors with CV>20% we obtained 4 groups where the third conglomerate showed qualities with high values of commercial interests. Qualitatively, the tree did not show variability. The multivariate correspondence analysis in both cantons exhibited similar patterns of correspondence between accessions and leaves characteristics. It was also found correlations mostly positive between fruit length and fruit weight, exocarp and pulp. Following high quality parameters proposed by Gardizabal & Rosenberg (1993), INEN (2008), INIAP (2005) and Scheldeman (2002) QSB03- QSB y SMC01-SME01 materials were selected for Quilanga and Saraguro respectively, pondering weight, firmness, soluble solids, acidity, and quantity of optimum seeds. Qualitatively, fruits were asymmetric, plain, and printed and with brownish green color. We did not have significance for the altitude zones regarding the fruit’s characteristics. The isohyets and isotherms of the potential accessions showed presence in zones with precipitations of 1201 mm/yr and temperatures between 16-20 C, which are the optimum for chirimoya. Keywords: Annona, descriptors, characterization, potentials, fruit, quality, genetic variability